Changing Cycles of Terrorism: The use of Vehicles as a Tool for Violent Attacks (Global Journal of Human-Social Science, 2018)
Terrorist activities are usually carried out by men of the underworld who derive pleasure is taking the lives of innocent people through the use of car bombs, suicide bombers and in rare cases sporadic shooting at crowded places. These methods over the years have proved to be very effective and capital intensive with serious logistic planning and critical intelligence and evaluation of the target area before the time or date to strike. However, with the whole world especially the super powers on high alert, the terrorists have changed their tactics and have selected a more discrete but effective method to deploy violence through the use of vehicles to ram into crowds of unsuspecting innocent people. To this end, this it is the aim of this paper to attempt to demonstrate how terrorist have changed their game by now using a motorized technique in their violent operations. The study adopted the use of secondary data and the descriptive method in the analysis of its variables. The research concluded that terrorists have adopted the use of vehicles to ram into crowded places because the method raises little or no suspicion before the attack. The paper recommends that speed breakers should be installed at bus stops and also government of states need to invest in intelligence gathering and proactive to avoid such attacks in the future.
Keywords: terrorism; violence; vehicle; deployment; attack